Applications and toxicity of graphene family nanomaterials and their composites - Singh Z (Dove Medical Press, 2016)
Zorawar Singh Department of Zoology, Khalsa College, Amritsar, Punjab, India Abstract: Graphene has attracted much attention of scientific community due to its enormous potential in different fields, including medical sciences, agriculture, food safety, cancer research, and tissue engineering. The potential for widespread human exposure raises safety concerns about graphene and its derivatives, referred to as graphene family nanomaterials (GFNs). Due to their unique chemical and physical properties, graphene and its derivatives have found important places in their respective application fields, yet they are being found to have cytotoxic and genotoxic effects too. Since the discovery of graphene, a number of researches are being conducted to find out the toxic potential of GFNs to different cell and animal models, finding their suitability for being used in new and varied innovative fields. This paper presents a systematic review of the research done on GFNs and gives an insight into the mode and action of these nanosized moieties. The paper also emphasizes on the recent and up-to-date developments in research on GFNs and their nanocomposites for their toxic effects. Keywords: graphene, quantum dots, desalination, drug delivery, antibacterial, cytotoxicity, genotoxicity